A Citizen-Centered Theory. Issue 2 (14th October 2020) - Mansbridge, Jane
Because our collective needs for state coercion will steadily increase with greater human interdependence, we must take far more seriously the need to justify that coercion to the coerced. Cristina Lafont moves to the forefront of democratic theory the goal that citizens should 'own and identify with the institutions, laws and policies' that coerce them – an important move, particularly today, when many feel, often correctly, that they have not been 'heard' in producing the laws that coerce them. Lafont's approach might be furthered, I argue, by a theory of legitimacy that a) explicitly endorses plural sources of democratic legitimacy, b) acknowledges the aspirational quality of the many democratic ideals that make up this legitimacy, and c) recognizes consequently that democratic legitimacy is always partial .